Data-Driven Platform Framework for Digital Whole-Process Expressway Construction Management - Chen, Shu-Yang; Zhang, Jing-Xiao; Ni, Qi-Chang; Skitmore, Martin; Ballesteros-Pérez, Pablo; Ke, Yong-Jian; Zuo, Jian; Sun, Hao-Jie (Frontiers in Neuroscience, 2022)
To increase the speed and efficiency of expressways construction, information management is being gradually introduced into the construction process. However, progress is limited due to the complexity of expressway engineering and application limitations of information technology. Design and delivery are still dominated by paper files, and the management of test and inspection data is still relatively extensive. Research to date into digital expressway construction has been piecemeal and fragmented with a lack of research related to the whole construction process and a data-centric information management system yet to be realized. In response, through literature research and semi-structured interviews, the framework of a data-driven digital whole-process highway construction management platform was determined. A whole process management platform was established according to the framework, and the functional application of the proposed platform was explained through a case. The framework is proposed from the perspective of the whole process of collaborative sharing., which provides a new way of thinking to solve the problems existing in the current field of expressway construction whole-process management. It also provides data-centric management, electronic design and delivery, a refined workflow, and an efficient management process.